Heavy metal em Cuiabá : cena musical e lugares do underground na cidade - Gomes, Iuri Barbosa (2018)
The city of Cuiabá, capital of the state of Mato Grosso, is embedded in the borders of the Mato Grosso Pantanal and the South American Geodesic Center. About three centuries later, it reverberates contradictions of an urbanization marked by the coexistence of memories of the old with the virtualities of the modern. The city moved from the garimpo in the 18th Century to the emergent metropolis in the Brazilian Midwest of the 21st Century. In the hinterland of Mato Grosso, Cuiabá holds the cosmopolitanism of intercultural relations as symbolic capital inscribed in its historical formation and geographical characterization. It is in this social space that emerges a musical scene that calls itself underground, already in the passage from the 20th Century to the 21st. This research on contemporary culture uses an interdisciplinary approach, from the field of communication, to investigate the musical scene of the heavy metal cuiabano. In the model of communication studies as culture (LIMA, 2001), communication is defined as a symbolic process in which reality is produced, maintained, repaired and transformed. This theoretical approach suggests the realization of a historical-critical analysis for the elucidation of the meanings involved in cultural practices. Thus, this thesis presents a narrative about bands of authorial character that formed the metallic scene - which, in turn, emerges in the midst of the rock scene in the city. The cuiabana heavy metal scene consists of performing, communicational and musical practices. These practices form a deviant know-how hornbook that has been updated in places where heavy metal could be heard in the urban space in Cuiabá in the first decade of the 2000s. The emphasis of the research is in the period between 2004 (year of inauguration of Cavernas Bar) and 2014 (year in which the research was started), but also the rock route in the city is presented, because it is from the very dynamics of the rock scene that heavy metal emerges in the musical scene cuiabano and reverberates by the city. This route is built from structured, semi-structured and open (unstructured) interviews recorded in audio and video - and also made by Skype, Whatsapp and e-mail. Primary sources (fanzines, posters, CDs and other items) were also used, as well as an on-site experience of the researcher. In this thesis, we use concepts from geography - place, in the meanings of Yi-Fu Tuan (1983), Doreen Massey (1994) and Milton Santos (2014) - and ethnomusicology - music scene according to Will Straw (1984, 2002, 2011, 2014) And Andy Bennett (2004), and sound landscape by Raymond Murray Schafer (2001). From these concepts it is sought to understand the know-how of instrumentalists and performers, among dilettantes and enthusiasts, of "heavy music" and the practices that were part of the underground environment and its places in the garimpo-city.